Acrylic acid-olefin hybrid polymers and their use as antirust agents
By using acrylic-olefin backbone polymers and combining synthetic wax as diluents, the existing anti-rust agents have been solved inadequate performance in heavy-duty applications and extreme environments, achieving more effective anti-rust and UV stability, suitable for High-performance anti-rust agent.
Patent Information
- Application Number
- CN202380038901.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-06
- Filing Date
- 2023-05-03
- Publication Date
- 2024-12-17
AI Technical Summary
Existing anti-rust agents are difficult to provide adequate protection against rust in heavy-duty applications and extreme environmental conditions, especially when high melting point waxes are used, and are undersupply limited and performance is insufficient.
The wax-acrylate polymer is prepared by synthesizing wax as diluent using polymers from the acrylic-olefin backbone as anti-rust agent, which contains at least 30% α-olefin to improve its anti-rust in heavy-duty applications. performance.
Significantly improves rust resistance and UV stability in heavy-duty applications, can perform well in corrosion performance tests over 250 hours and provide longer-lasting protection in extreme environments.
Smart Images

Figure BDA0005121813880000031 
Figure BDA0005121813880000061 
Figure BDA0005121813880000062
Abstract
Description
Technical Field
[0001] The disclosed technical field generally relates to acrylic-olefin hybrid polymers useful as rust inhibitors in coatings and metalworking fluids. Background Art
[0002] Many rust inhibitors for heavy-duty applications are based on high melting point waxes. The most common waxes for heavy-duty applications are microcrystalline waxes or petrolatum waxes. These wax stocks are closely related to Class I refineries and can be subject to strong supply constraints when there are changes in refining industry supplies. Acrylate polymers are common, however, these polymers alone are not sufficient to provide sufficient rust protection in heavy-duty applications or under extreme environmental conditions. Synthetic wax stocks (such as alpha-olefin waxes) can be added to acrylic polymers to improve performance, however, such mixtures still do not have sufficient performance in heavy-duty applications.
[0003] Thus, the disclosed technology solves the problem of rust prevention in heavy-duty applications using alpha-olefin waxes. Summary of the invention
[0004] Applicants have discovered that the use of synthetic wax as a diluent in the preparation of acrylate polymers forms wax-acrylate polymers that are unexpectedly more effective in reducing rust in heavy-duty applications than compositions produced by simply mixing acrylate polymers and synthetic wax. Thus, polymers having an acrylic-olefin backbone prepared from a monomer composition comprising at least one C 1-30 A (meth)acrylic acid compound and at least one α-olefin (“C 20+ The resulting polymer has at least 30 wt. % (or at least 35 wt. %, or 40 wt. %, or 45 wt. %, or at least 49 wt. % or 50 wt. %) of α-olefin incorporated therein.
[0005] In some embodiments, at least one (meth)acrylic acid compound may be C 1-20 (Meth)acrylate, or C 1-18 (Meth)acrylate, or C 4-12(Meth) acrylic acid ester or their mixture. Suitable (meth) acrylic acid compounds include (meth) acrylic acid ester, (meth) acrylic acid, (meth) acrylamide or their combination. In some embodiments, the (meth) acrylic acid compound can be (meth) acrylic acid ester, such as but not limited to butyl acrylate, n-butyl methacrylate, stearyl methacrylate, methyl methacrylate or their mixture. In some embodiments, (meth) acrylic acid ester can include butyl acrylate, n-butyl methacrylate or their mixture. In other embodiments, (meth) acrylic acid ester can include stearyl methacrylate, methyl methacrylate or their mixture.
[0006] The polymer backbone may contain at least 30 wt % (or at least 35 wt %, or 40 wt %, or 45 wt %, or at least 49 wt %, or 50 wt %) of α-olefins. In some embodiments, the polymer backbone may contain at least 49 wt % or 50 wt % of α-olefins. Suitable α-olefins include, but are not limited to, C 20-28 α-olefins, C 20-24 α-olefins, C 24-28 α-olefins, C 26-28 α-olefins, α-olefins having a chain length of at least 30 carbon atoms (“C 30+ α-olefins") or mixtures thereof.
[0007] In some embodiments, the at least one α-olefin may include C 24-28 In other embodiments, the monomer composition may include C 24-28 α-olefin and an acrylate monomer, the acrylate monomer being butyl acrylate, n-butyl methacrylate, or a mixture thereof. In such embodiments, the polymer backbone may comprise at least 40 wt % or at least 50 wt % of C 24-28 α-Olefins.
[0008] The molecular weight of suitable polymers is not overly limited. For example, the polymers may have a weight average molecular weight M in the range of 10,000 Daltons to 100,000 Daltons. w In some embodiments, M w The range of may be 10,000 Daltons to 80,000 Daltons or 10,000 Daltons to 75,000 Daltons, or 15,000 Daltons to 70,000 Daltons.
[0009] The polymer disclosed herein can be used as a rust inhibitor. Therefore, a rust-proofing composition comprising any of the polymers described above is disclosed. The rust-proofing composition may optionally include one or more of the following components: based on the gross weight of the composition, at least one detergent used at a concentration of 20 wt % to 40 wt % and / or at least one polyisobutylene thickener used at a concentration of 0 wt % to 20 wt %. The rust-proofing composition may have a corrosion performance greater than 250 hours measured using ASTM B117. In some embodiments, the rust-proofing composition may have an improved UV stability performance measured using ASTM G154 compared to a rust-proofing composition without the disclosed polymer.
[0010] Also disclosed are methods and uses of reducing corrosion of metal parts by coating the parts with a rust-inhibiting composition comprising the polymer described above. DETAILED DESCRIPTION
[0011] Various features and embodiments are described below by way of non-limiting illustration. Disclosed is a polymer having an acrylic acid-olefin backbone prepared from a monomer composition comprising at least one C 1-30 A (meth)acrylic acid compound and at least one α-olefin (“C 20+ α-olefins”).
[0012] At least one (meth)acrylic acid compound may be C 1-30 (Meth) acrylic acid compounds, C 1-20 (Meth) acrylic acid compound, or C 1-18 (Meth) acrylic acid compound, or C 4-12 (Meth) acrylic acid compounds or mixtures thereof. The (meth) acrylic acid compounds may include at least one (meth) acrylate, (meth) acrylic acid, (meth) acrylamide, or a combination thereof. As used herein, the term "acrylic acid" includes derivatives, salts, or amides of acrylic acid or methacrylic acid. In addition, the term "(meth) acrylate" and related terms include both acrylate groups and methacrylate groups, i.e., the methyl group is optional. Therefore, in some embodiments, the acrylic acid compound may include at least one acrylate, acrylic acid, acrylamide, methacrylate, methacrylic acid, methacrylamide, or a combination thereof.
[0013] In yet other embodiments, the acrylic acid may be a (meth)acrylate having formula (I):
[0014]
[0015] Where R is hydrogen or C1-C 30 The hydrocarbon group and R 1 It is C1-C30 Hydrocarbyl group. R or R 1 Additional range includes C 1-20 Hydrocarbyl groups, or C 1-18 Hydrocarbyl groups, or C 4-12 In another embodiment, R can be hydrogen or a methyl group, and R 1 Can be C 1-20 Hydrocarbyl groups, or C 1-18 Hydrocarbyl groups, or C 4-12 Hydrocarbyl group.
[0016] As used herein, the term "alkyl" refers to a group having a carbon atom directly connected to the rest of the molecule, wherein the group includes at least a carbon atom and a hydrogen atom. If the alkyl group contains more than one carbon atom, those carbons do not necessarily need to be connected to each other. For example, at least two carbons can be connected via a suitable element or group. In various embodiments, the term "alkyl" refers to a group having a carbon atom directly connected to the rest of the molecule, wherein the group is composed of carbon, hydrogen, optionally one or more heteroatoms, provided that the heteroatom does not change the main hydrocarbon properties of the substituent. The heteroatom can connect at least two carbons in the alkyl group and optionally no more than two non-hydrocarbon substituents. Suitable heteroatoms will be apparent to those skilled in the art and include, for example, sulfur, nitrogen, oxygen, phosphorus and silicon. When the alkyl contains heteroatoms, optionally, no more than two heteroatoms will be present for every ten carbon atoms in the alkyl group. Suitable non-hydrocarbon substituents will also be apparent to those skilled in the art, and include, for example, halo, hydroxyl, alkoxy, sulfhydryl, alkylthiol, nitro, nitroso and oxygen sulfonic acid (sulphoxy).
[0017] Thus, examples of hydrocarbyl groups in the context of the present technology include:
[0018] (i) a hydrocarbon group selected from aliphatic (eg alkyl or alkenyl) groups, alicyclic (eg cycloalkyl, cycloalkenyl, cycloalkadienyl) groups and aromatic groups;
[0019] (ii) a substituted hydrocarbyl group selected from the group consisting of a hydrocarbyl group as defined in (i) substituted with not more than two non-hydrocarbon substituents and / or one or more hydrocarbon substituents selected from the group consisting of halo, hydroxy, alkoxy, mercapto, alkylmercapto, nitro, nitroso and oxysulfonate;
[0020] (iii) a heterohydrocarbon-containing group selected from the hydrocarbon groups defined in (i) containing one or more heteroatoms in the ring or chain, provided that the group contains no more than two heteroatoms selected from sulfur, nitrogen, oxygen, phosphorus and silicon for every ten carbon atoms in the group. The heterohydrocarbon-containing group may be substituted with no more than two non-hydrocarbon substituents and / or one or more hydrocarbon substituents.
[0021] In some embodiments, the term "hydrocarbyl" refers to a group having a carbon atom directly attached to the remainder of the molecule, wherein the group consists of carbon atoms and hydrogen atoms.
[0022] Suitable (meth)acrylates include, but are not limited to, methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-methylpentyl (meth)acrylate, 2-propylheptyl (meth)acrylate, 2-butyloctyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, isooctyl (meth)acrylate, isononyl (meth)acrylate, 2-tert-butylheptyl (meth)acrylate, 3-isopropylheptyl (meth)acrylate, decyl (meth)acrylate, undecyl (meth)acrylate, 5-methylundecyl (meth)acrylate, dodecyl (meth)acrylate, 2-methyldodecyl (meth)acrylate, tridecyl (meth)acrylate, 5-methyldecyl (meth)acrylate trialkyl esters, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, 2-methylhexadecyl (meth)acrylate, heptadecyl (meth)acrylate, 5-isopropylheptadecyl (meth)acrylate, 4-tert-butyloctadecyl (meth)acrylate, 5-ethyloctadecyl (meth)acrylate, 3-isopropyloctadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, (meth)acrylates derived from unsaturated alcohols such as oleyl (meth)acrylate; and cycloalkyl (meth)acrylates such as 3-vinyl-2-butylcyclohexyl (meth)acrylate or bornyl (meth)acrylate.
[0023] In some embodiments, (meth)acrylates include, but are not limited to, butyl acrylate, n-butyl methacrylate, stearyl methacrylate, methyl methacrylate, or mixtures thereof. In some embodiments, the monomer composition may include butyl acrylate, n-butyl methacrylate, or mixtures thereof. In other embodiments, at least one (meth)acrylate may include stearyl methacrylate, methyl methacrylate, or mixtures thereof.
[0024] Other examples of suitable (meth)acrylates include alkyl (meth)acrylates with long-chain alcohol-derived groups, which can be obtained, for example, by reaction of (meth)acrylic acid (by direct esterification) or methyl (meth)acrylate (by transesterification) with long-chain fatty alcohols, whereby reaction mixtures of esters such as (meth)acrylates with alcohol groups having various chain lengths are generally obtained. These fatty alcohols include Sasol's 1620, 10. 810, 12. 1012EE, 1014CDC, 1214, 1214GC, 1214HA, 1216 and 125; Shell AG 91. twenty three, 25. 45 and 135; BASF's C13-C15 alcohol, isotridecanol, and KaoCorporation 2465, 2470, 8655 and Ecogreen Oleochemicals 80. twenty four, 26. 28 and 68.
[0025] Further examples of (meth)acrylates include alkyl (methacrylates) having a branched alcohol-derived group, which can be obtained, for example, by reaction of (meth)acrylic acid (by direct esterification) or methyl (meth)acrylate (by transesterification) with a Guerbet alcohol. Examples of Guerbet alcohols include 2-butyloctanol, 2-butyldecanol, 2-hexyloctanol, 2-hexyldecanol, 2-octyldecanol, 2-hexyldodecanol, 2-octyldodecanol, 2-decyltetradecanol, 2-dodecylhexadecanol and 2-tetradecyloctadecyl alcohol.
[0026] The (meth)acrylate can be aromatic, including, for example, benzyl methacrylate. In another embodiment, the aromatic (meth)acrylate can be selected from phenyl methacrylate, phenylpropyl methacrylate or styrene. It is contemplated that other oil-insoluble (meth)acrylates polymerizable in oil can also be used. Mixtures of these and other oil-insoluble monomers can also be used to prepare the disclosed polymers.
[0027] In one embodiment, suitable (meth)acrylates may include dispersant monomers; dispersant monomers include those monomers that can be polymerized with (meth)acrylate monomers and contain one or more heteroatoms in addition to the carbonyl group of the (meth)acrylate. The dispersant monomers may contain nitrogen-containing groups, oxygen-containing groups, or mixtures thereof.
[0028] In some embodiments, the (meth)acrylic acid compound may be (meth)acrylic acid or an oxygen-containing (meth)acrylic acid ester monomer. The (meth)acrylic acid may include an acrylic acid having formula (II):
[0029]
[0030] Where R can be hydrogen or C1-C 30 Hydrocarbyl group.
[0031] Oxygen-containing compounds may include hydroxyalkyl (meth)acrylates such as 3-hydroxypropyl (meth)acrylate, 3,4-dihydroxybutyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2,5-dimethyl-1,6-hexanediol (meth)acrylate, 1,10-decanediol (meth)acrylate, carbonyl-containing (meth)acrylates such as 2-carboxyethyl (meth)acrylate, carboxymethyl (meth)acrylate, oxazolidinylethyl (meth)acrylate, N-(methacryloyloxy)formamide, acetonyl (meth)acrylate, N-methyl acryloylmorpholine, N-methacryloyl-2-pyrrolidone, N-(2-methacryloyl-oxyethyl)-2-pyrrolidone, N-(3-methacryloyloxypropyl)-2-pyrrolidone, N-(2-methacryloyloxypentadecyl)-2-pyrrolidone, N-(3-methacryloyloxy-heptadecyl)-2-pyrrolidone; glycol di(meth)acrylates such as 1,4-butanediol (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-ethoxyethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate or mixtures thereof.
[0032] In some embodiments, the (meth)acrylic compound may be (meth)acrylamide or a nitrogen-containing (meth)acrylate monomer. The (meth)acrylamide may include an acrylamide having formula (III):
[0033]
[0034] Each R can be hydrogen or C1-C 30 Hydrocarbyl group.
[0035] Examples of suitable nitrogen-containing compounds include N,N-dimethylacrylamide, N-vinylcarbonamides such as N-vinylformamide, vinylpyridine, N-vinylacetamide, N-vinylpropionamide, N-vinylhydroxyacetamide, N-vinylimidazole, N-vinylpyrrolidone, N-vinylcaprolactam, N-vinylfuran, vinyloxazole, N,N-dimethylaminoethyl(meth)acrylate, N,N-dimethylaminopropyl(meth)acrylate, N,N-diethylaminoethyl(meth)acrylate, 2-diisopropylaminoethyl(meth)acrylate, 2-tert-butylaminoethyl(meth)acrylate, N-2-dimethylaminoethyl(meth)acrylamide, N-3-dimethylaminopropyl(meth)acrylamide, N,N-dimethylaminobutyl(meth)acrylamide, N-2-diethylaminoethyl(meth)acrylamide, or mixtures thereof.
[0036] As described above (meth) acrylates can be reacted with α-olefins to produce polymers. In some embodiments, at least one (meth) acrylate is a single chemical species. In yet other embodiments, blends of one or more of the (meth) acrylates described above can be used.
[0037] The α-olefins (sometimes referred to as mono-1-olefins) used to prepare the polymers may include isomerized α-olefins. Examples of suitable α-olefins include ethylene, propylene, butene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-tridecene, 1-tetradecene, 1-pentadecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecene, 1-eicosene, 1-hexonedecene, 1-dodecene, 1-tetradecene, etc. Commercially available α-olefin fractions that can be used include those that are "waxier" in nature, and typically include α-olefins (C 20 or more) having 20 carbon atoms or more. 20+ α-olefin) segment, such as C 20-28 α-olefins, C 20-24 α-olefins, C 24-28 α-olefins, C 26-28 α-olefins, α-olefins having a chain length of at least 30 carbon atoms (“C 30+The production of these types of α-olefins is well known in the industry. Exemplary α-olefins that can be commercially obtained include those produced by Chevron Phillips Chemical Company, LP. α-Olefins.
[0038] In some embodiments, the monomer composition may include C 24-28 In other embodiments, the monomer composition may include C 24-28 α-olefin and an acrylate monomer, the acrylate monomer being butyl acrylate, n-butyl methacrylate, or a mixture thereof. In such embodiments, the polymer backbone may comprise at least 40 wt % or at least 50 wt % of C 24-28 α-Olefins.
[0039] In some embodiments, the third monomer can be used to prepare an acrylic acid-olefin polymer suitable as a rust inhibitor, as long as the resulting polymer has a main acrylic acid-olefin backbone containing at least 30% by weight (or at least 35% by weight, or 40% by weight, or 45% by weight, or at least 49% by weight or 50% by weight) of an alpha-olefin incorporated therein. Suitable third monomers are not overly limited and include any monomer that readily reacts with (meth) acrylic acid compounds and alpha-olefins. In some embodiments, the third monomer can be present in the monomer composition at 0.1% to 10% by weight, 0.1% to 8% by weight, 0.5% to 6% by weight, and 0.5% to 5% by weight.
[0040] The molecular weight of suitable polymers is not overly limited and may include any molecular weight suitable for coating applications. Thus, in some embodiments, the polymer may have a weight average molecular weight M in the range of 10,000 Daltons to 100,000 Daltons. w In some embodiments, M w The range of may be 10,000 Daltons to 80,000 Daltons or 10,000 Daltons to 75,000 Daltons, or 15,000 Daltons to 70,000 Daltons.
[0041] The weight average molecular weight of the materials described herein was determined using gas permeation chromatography (GPC) using a Waters Empower TMData acquisition and analysis software was used for Waters GPC 2000 measurement. The column was polystyrene (PLgel, 5 microns, purchased from Agilent / Polymer Laboratories, Inc.). For the mobile phase, individual samples were dissolved in tetrahydrofuran and filtered with a PTFE filter, and then they were injected into the GPC port.
[0042] Waters GPC 2000 operating conditions :
[0043] Injector, column, and pump / solvent compartment temperature: 40°C
[0044] Autosampler control: Run time: 40 minutes
[0045] Injection volume: 300 μl
[0046] Pump: System pressure: Approx. 90 bar (Maximum pressure limit: 270 bar, Minimum pressure limit: 0 psi)
[0047] Flow rate: 1.0ml / min
[0048] Differential Refractometer (RI): Sensitivity: -16; Scale Factor: 6
[0049] The polymer disclosed herein can be used as a rust inhibitor. The rust-proof composition can be used with 100% active material, or it can be a diluent. As used herein, "diluent" is based on the weight percentage of the active material, for example, a 60% by weight diluent will have 60% by weight of active material and 40% by weight of diluent. The rust-proof composition can be diluted to, for example, a 60% by weight, 50% by weight, or 40% by weight diluent. Therefore, in some embodiments, the diluent can be a diluent between 40% by weight and 60% by weight or between 50% by weight and 60% by weight. In other embodiments, the diluent can be a diluent between 40% by weight and 50% by weight, for example, a diluent of 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48% by weight, or 49% by weight. Therefore, a rust-proof composition comprising any of the above-mentioned polymers is disclosed, which may or may not be diluted as described above.
[0050] Suitable diluents include solvent naphtha with a flash point of 60°C. In some embodiments, the rust preventive composition may also optionally contain a volatile diluent. "Volatile diluent" means a generally liquid component having a volatility greater than the volatility of an oil such as mineral oil. The volatile diluent may contain water or one or more organic solvents. The diluent may therefore contain a volatile organic solvent such as naphtha (also known as petroleum ether), mineral spirits, kerosene or ethyl lactate. Among these materials may be hydrocarbon solvents. Such materials may have a boiling point ranging from 30°C to 60°C or higher, up to a boiling point ranging from 175°C to 280°C. Some such volatile diluents may have a boiling range of 130°C to 210°C; other volatile diluents have a boiling range of 196°C to 205°C. In general, if the boiling point of the diluent is below 280°C, it may be considered volatile.
[0051] If desired, volatile diluents may be present in the concentrate of the above components, but the most common diluents or most of the diluents will be added when preparing a fully formulated diluted antirust composition. The amount of diluent will generally be an amount that provides appropriate viscosity and rheological properties so that the antirust composition can be applied to a substrate such as a metal product or surface. Therefore, if the concentrate is diluted to 40% in the final coating composition, the total amount of diluent will generally increase by 60% of additional solvent or diluent for dilution (except for the oil of the dissolved metal salt that does not count the amount of the volatile diluent). Of course, the overall total amount of diluent (if present) will depend on the amount of diluent used to prepare the final antirust composition, and therefore can be present in 60% by weight, 50% by weight or 40% by weight based on the total weight of the antirust composition. The amount of other components will generally be less than 100% by weight of the amount of the optional volatile diluent, such as at least 40% by weight to 60% by weight or higher and other amounts that can be easily determined by those skilled in the art.
[0052] That is, in the absence of an optional volatile diluent or only a small amount, such as up to 10% by weight or 5% by weight or 2% by weight or 1% by weight or 0.1% by weight of the composition, one of the ways of the present technology that can be adopted is by preparing an initial mixture of the components described herein. For this reason, the amount of the other components can be expressed as a percentage of the composition not including the amount of the optional volatile diluent. It is in this form (volatile diluent or solvent-free) that the materials of the disclosed technology can usually be commercially prepared and distributed. However, the material without diluent can have a viscosity that is not suitable for easy handling, so before the composition is applied as a coating to the substrate, it can be expected to add a volatile diluent. If there is a diluent when applying the coating, the actual amount of the other components can be calculated to take into account the presence of the diluent.
[0053] In some embodiments, the anti-rust composition may optionally include one or more of the following components: at least one detergent in an amount ranging from 20 wt % to 40 wt % and / or at least one thickener in an amount ranging from 0 wt % to 20 wt %, based on the total weight of the anti-rust composition.
[0054] The detergent can include at least one phenate, salicylate, salixarate, sulfonate or a combination thereof. In some embodiments, the detergent is a sulfonate detergent. Sulfonate can generally be an alkyl aryl sulfonate with one or more alkyl groups or alkyl groups with sufficient length to provide solubility in hydrocarbon oil. The salt can be a metal salt, or alternatively, a non-metallic salt, such as an amine (or ammonium) salt." sufficient length " can be in the alkyl group or alkyl group of the combination or alternatively, if there is more than one group, then at least 12 carbon atoms and up to 200 carbon atoms in the longest group in such groups, such as 18 to 100 or 24 to 48 carbon atoms. In one embodiment, each alkyl group or alkyl group can contain at least 8 or at least 12 carbon atoms and up to 200 carbon atoms or 18 to 100 or 24 to 48 carbon atoms separately. Examples of sulfonates include relatively low molecular weight salts such as calcium monononylnaphthalene sulfonate, calcium dinonylnaphthalene sulfonate or calcium trinonylnaphthalene sulfonate (or mixtures of mono-, di- and tri-alkyl species) and relatively higher molecular weight salts such as calcium oligomerized benzene sulfonate or calcium polymerized benzene sulfonate or calcium oligomerized toluene sulfonate or calcium polytoluene sulfonate.
[0055] These can be neutral salts or overbased salts. Neutral salts are those containing approximately or exactly stoichiometric amounts of metal ions to neutralize the acid functional groups of the alkylaryl sulfonic acid. Overbased salts are prepared by reacting with: a stoichiometric excess of metal, such as calcium, barium, magnesium, potassium, zinc or sodium, in the form of an alkaline compound, such as an oxide, hydroxide or, ultimately, a carbonate obtained by treating with carbon dioxide in the case of calcium. Therefore, in some embodiments, the metal detergent can be a metal overbased detergent. Overbased materials are well known in the lubricant industry as overbased detergents and can also be used as surfactants or wetting agents. In certain embodiments, the salt can be a calcium salt, a barium salt or a sodium salt. In yet other embodiments, the salt can be a calcium salt or a magnesium salt. The TBN range of the metal detergent can be 15 mg KOH / g to 500 mg KOH / g or 25 mg KOH / g to 400 mg KOH / g. TBN is an expression commonly used to describe the alkalinity of lubricant additives and / or lubricants. It is the amount of potassium hydroxide (mg KOH) required to neutralize one gram of sample being tested using titration and bromophenol blue as an indicator. Such TBN titration methods are well known in the art and have been standardized in the industry, such as in ASTM D2896.
[0056] In some embodiments, the metal sulfonate can be an alkyl aryl sulfonate containing an alkyl group of 9 to 200, or 12 to 200, or 18 to 100, or 25 to 50, or 30 to 40 carbon atoms. Such materials are usually provided in commercial form in the presence of a certain amount of diluent oil, usually mineral oils such as API I class oils, and the material is usually prepared in the oil. The amount of diluent oil that can be associated with the metal alkyl aryl sulfonate and accompanying can be a ratio of 1:5 to 5:1 of salt to oil. Therefore, in some embodiments, the metal detergent can be a calcium sulfonate detergent. The calcium sulfonate detergent can be neutral or highly basic. In other embodiments, the metal detergent is a highly basic calcium sulfonate detergent.
[0057] On an oil-free basis, the amount of detergent (e.g., metal sulfonate) in the disclosed rust preventive composition can range from 2 wt% to 30 wt%, or 3 wt% to 30 wt%, or 3 wt% to 25 wt%, or 4 wt% to 20 wt%, or 5 wt% to 15 wt%. As noted above, the amounts cited do not include the amount of any volatile diluent that may be present. In yet other embodiments, the detergent may be present in an amount ranging from 20 wt% to 40 wt% of at least one detergent, based on the total weight of the rust preventive composition.
[0058] In some embodiments, the rust preventive composition may include one or more components to enhance corrosion protection. Suitable components are not overly limited and may include fatty acids, dimerized fatty acids, dicarboxylic acids, oxidized waxes, and esterified waxes.
[0059] In some embodiments, the disclosed rust-preventive composition may include a thickener for ease of handling and improved adhesion of the coating to metal parts. Suitable thickeners are not overly limited and may include bright stock and other high viscosity petroleum oils, polymeric thickeners such as polytetrafluoroethylene, polystyrene, styrene-butadiene polymers, and olefin polymers. In some embodiments, the thickener may be a polyisobutylene thickener having a number average molecular weight of about 2000 Daltons.
[0060] The rust preventive composition may have a corrosion performance of greater than 250 hours measured using ASTM B 117. In some embodiments, the rust preventive composition may have improved UV stability performance measured using ASTM G154 compared to a rust preventive composition without the disclosed polymer.
[0061] Also disclosed are methods and uses of reducing corrosion of metal parts by coating the parts with a rust-inhibiting composition comprising the polymer described above.
[0062] Unless otherwise indicated, the amount of each chemical component recited does not include any solvent or diluent oil which may be customarily present in the commercial material, i.e., on an active chemical basis. However, unless otherwise indicated, each chemical or composition referred to herein should be interpreted as being a commercial grade material which may contain the isomers, by-products, derivatives, and other such materials which are normally understood to be present in the commercial grade.
[0063] It is known that some of the above-mentioned substances may interact in the final formulation so that the components of the final formulation may be different from those initially added. For example, metal ions (e.g., metal ions of detergents) may migrate to other acidic or anionic sites of other molecules. The products thus formed, including the products formed when the compositions of the present invention are used for their intended purposes, may not be easy to describe. However, all such modifications and reaction products are included within the scope of the present invention. The present invention includes compositions prepared by mixing the above-mentioned components.
[0064] The invention herein is used to reduce corrosion in heavy duty applications and may be better understood with reference to the following examples.
[0065] Example
[0066] Example Group 1: Acrylic polymers without α-olefins
[0067] Six solvent soluble acrylic polymers were prepared with a mixture of stearyl methacrylate (to provide solvent solubility) and other acrylic monomers and functionalized with small amounts of methacrylic acid or 3-dimethylaminopropyl methacrylamide (DMAPMA). The acrylate polymers were synthesized at 60 wt % active in the dearomatized hydrocarbon solvent Exxsol 60D. The compositions used to prepare the acrylate polymers are shown in Table 1 below. The amounts shown are weight percent (wt %).
[0068] Table 1: Acrylate polymer composition
[0069] Monomer mixture (wt%) Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Stearyl Methacrylate 48 42 42 48 42 42 Methyl Methacrylate 9 9 Lauryl Methacrylate 15 15 C32 Guerbet alcohol 15 15 Methacrylic acid 3 3 3 DMAPMA 3 3 3 Exxsol D60 40 40 40 40 40 40
[0070] The obtained acrylic polymer was then mixed with 10 wt% of C 24 α-olefins to C 28α-olefin blends. And the corrosion performance is evaluated to determine whether the α-olefin can provide enough wax to give a strong protective coating. The salt spray performance of polymer / olefin blends and their standard operation using ASTM B117-operating salt spray (fog) equipment is shown in Table 2 below. In this method, the polymer coating is stretched to a specified thickness on an AISI 1008 carbon steel Q panel (purchased from Q-Lab Corporation) and allowed to dry for 24 hours. The panel is then placed in a salt spray chamber maintained at a temperature of 35°C and continuously sprayed with a 5% NaCl solution. When more than 5% rust appears on the surface, the panel is considered to have failed. None of the blends in Table 2 can provide the salt spray performance for the recommended protection of heavy products.
[0071] Table 2: Acrylate Polymer / α-Olefin Blends
[0072]
[0073] Example Group 2: Acrylic Acid-Olefin Hybrid Polymer
[0074] Polymer synthesis
[0075] The disclosed acrylate / alpha-olefin polymer can be prepared by melting the alpha-olefin and adding it to a 4-neck round-bottom flask equipped with a mechanical stirrer, a nitrogen inlet, a thermocouple, and a Claisen adapter with a peristaltic pump tube inlet and a water-cooled condenser. The (meth) acrylate is premixed with an initiator (tert-butyl peroxy-2-ethylhexanoate or tert-butyl peroxybenzoate) and then fed to the flask via a peristaltic pump in about 4 hours. Once the feeding is complete, the reaction is maintained at 90° C. to 125° C. for about 3 hours. The resulting polymer is a colorless solid that melts at about 48° C. to 53° C. The method can be modified and / or optimized by a person of ordinary skill in the art according to reaction conditions, equipment, or raw materials, etc. to prepare the desired polymer, i.e., a polymer having a main chain containing at least 30% by weight (or at least 35% by weight, or 40% by weight, or 45% by weight, or at least 49% by weight or 50% by weight) of an alpha-olefin.
[0076] Various polymers synthesized using the above method are readily available in Exxsol TM The dilutions were diluted to 60% and 40% in D60 solvent. The dilutions were stable for more than one month when stored at room temperature. The corrosion performance of the dilutions was also evaluated using the ASTM B117 salt spray method. The dilution at the 60% treatment rate was a soft solid that could be easily stretched to 8 mils wet thickness on a metal panel. The dilution at the 40% treatment rate was a thin liquid that required immersion. Table 3 shows the synthesized polymer compositions and the 60% and 40% dilution salt spray results.
[0077] Table 3: Acrylic-Olefin Hybrid Polymers and Salt Spray Results
[0078]
[0079]
[0080] This polymer performs significantly better than the acrylate polymer / alpha olefin blends of Table 2. This polymer does not perform well at lower processing rates, likely due to the thinness of the coating.
[0081] Scaled-up polymer batches were prepared and tested for salt spray performance at various dilutions. The polymer compositions and performance results or scaled-up batches are shown in Table 4 below.
[0082] Table 4: Acrylic-Olefin Hybrid Polymers and Salt Spray Results
[0083]
[0084]
[0085] As shown in Table 4 above, the polymer performs very well at 60 wt% and 50 wt% dilutions, and performance drops significantly at 40 wt% dilution. The optimal active concentration may be between 40 wt% and 50 wt% dilution, such as 41 wt%, 42 wt%, 43 wt%, 44 wt%, 45 wt%, 46 wt%, 47 wt%, 48 wt% or 49 wt% dilution.
[0086] UV stability is an important factor for heavy-duty rust inhibitors because the coatings are often used for outdoor corrosion protection in the elements. To evaluate UV stability, the coatings were stretched to 8 mils wet thickness on AISI 1008 carbon steel panels (purchased from Q-Lab Corporation) and allowed to dry for 24 hours. Once the coatings had dried, the panels were exposed to UV light at a wavelength of 340 nm according to the ASTM G154 Cycle A method (8 hours of UV exposure followed by 4 hours of darkness and condensation), which approximates the UV energy and intensity that the coatings are exposed to at noon 16 hours a day.
[0087] Three α-olefin acrylate polymers (Example 3, Example 8 and Example 9) and 606-55 ("AX60655") was evaluated for UV stability. AX60655 is a commercially available calcium sulfonate diluted in mineral oil that is used as a heavy-duty rust inhibitor. One of the Example 8 panels failed at 552 hours and was removed; however, the remaining panel was removed after 672 hours of exposure. Panels coated with the alpha-olefin acrylate polymer dilution showed less rust and discoloration than those coated with AX60655, indicating that alpha-olefin acrylate polymers can meet and possibly exceed the performance of traditional heavy-duty rust inhibitors under severe UV exposure conditions. The results are shown in Table 5 below.
[0088] Table 5
[0089]
[0090] Each document mentioned above is incorporated herein by reference, including any previous application claiming its priority, whether specifically listed above. The mention of any document is not to admit that the document meets the prior art or constitutes the general knowledge of any jurisdictional technician. Unless in the embodiment or otherwise clearly pointed out, all numerical values of the amount of specified substances, reaction conditions, molecular weight, carbon number, etc. in this specification sheet should be understood to be modified by the word "about". It should be understood that the upper and lower limits of the amount, range and ratio described herein can be independently combined. Similarly, the scope and amount of every kind of key element of the present invention can be used together with the scope or amount of any other key element.
[0091] As used herein, the transitional term "comprising," which is synonymous with "comprising," "containing," or "characterized by," is inclusive or open-ended and does not exclude additional, unrecited elements or method steps. However, in each use of "comprising" herein, it is intended that the term also encompasses the phrases "consisting essentially of" and "consisting of" as alternative embodiments, wherein "consisting of" excludes any element or step not specified, and "consisting essentially of" permits the inclusion of additional, unrecited elements or steps that do not materially affect the basic and novel characteristics of the composition or method under consideration.
[0092] Although certain representative embodiments and details have been shown for the purpose of illustrating the present invention, it will be apparent to those skilled in the art that various changes and modifications may be made without departing from the scope of the present invention. In this regard, the scope of the present invention is limited only by the following claims.
Claims
1. A polymer having an acrylic acid-olefin backbone prepared from a monomer composition, the monomer composition comprising: a. At least one C 1-30 (Meth)acrylic acid compounds; and b. at least one alpha-olefin ("C 20+ α-olefins”); and wherein the resulting polymer has at least 30 wt. % (or at least 35 wt. %, or 40 wt. %, or 45 wt. %, or at least 49 wt. % or 50 wt. %) of said α-olefin incorporated therein.
2. The polymer according to claim 1, wherein the at least one (meth)acrylic acid compound is C 1-20 (Meth) acrylic acid compound, or C 1-18 (Meth) acrylic acid compound, or C 4-12 (Meth)acrylic acid compound or a mixture thereof.
3. The polymer according to claim 1 or 2, wherein the at least one (meth)acrylic compound is a (meth)acrylate, (meth)acrylic acid, (meth)acrylamide or a combination thereof.
4. The lubricating composition according to any one of claims 1 to 3, wherein the at least one (meth)acrylic compound is acrylic acid, acrylamide, methacrylate, methacrylic acid, methacrylamide or a combination thereof.
5. The polymer according to any one of claims 1 to 3, wherein the at least one (meth)acrylic compound is a (meth)acrylic acid ester comprising butyl acrylate, n-butyl methacrylate, stearyl methacrylate, methyl methacrylate or a mixture thereof.
6. The polymer of claim 5, wherein the (meth)acrylate comprises butyl acrylate, n-butyl methacrylate, or a mixture thereof.
7. The polymer of claim 5, wherein the (meth)acrylate comprises stearyl methacrylate, methyl methacrylate, or a mixture thereof.
8. The polymer according to any one of claims 1 to 7, wherein the at least one α-olefin comprises C 20-28 α-olefins, C 20-24 α-olefins, C 24-28 α-olefins, C 26-28 α-olefins, α-olefins having a chain length of at least 30 carbon atoms ("C 30+ α-olefins") or mixtures thereof.
9. The polymer according to any one of claims 1 to 8, wherein the at least one α-olefin comprises C 24-28 α-Olefins.
10. The polymer of claim 9, wherein the polymer backbone comprises at least 40 wt. % or at least 50 wt. % C 24-28 α-Olefins.
11. The polymer according to any one of claims 1 to 10, wherein the polymer has a weight average molecular weight M in the range of 10,000 Daltons to 100,000 Daltons. w .
12. An anti-rust composition comprising the polymer according to any one of claims 1 to 11 and optionally one or more of the following components: a. at least one detergent; and / or b. At least one polyisobutylene thickener.
13. The rust preventive composition according to claim 12, wherein the at least one detergent is present in an amount of 20 to 40 wt% based on the total weight of the composition.
14. The rust preventive composition according to claim 13, wherein the detergent is an alkyl aryl sulfonate.
15. The rust preventive composition according to any one of claims 12 or 14, wherein the at least one polyisobutylene thickener is present in an amount of 0 wt% to 20 wt%, based on the total weight of the composition.
16. The rust preventive composition according to any one of claims 12 to 15, wherein the rust preventive composition has a corrosion performance of greater than 250 hours measured using ASTM B117.
17. The anti-rust composition according to any one of claims 12 to 16, wherein the anti-rust composition has improved UV stability performance measured using ASTM G154 compared to an anti-rust composition not containing the polymer.
18. A method of reducing corrosion of a metal part, the method comprising coating the metal part with the rust inhibiting composition according to any one of claims 12 to 17.
19. Use of a polymer according to any one of claims 1 to 11 in a rust protection composition for reducing corrosion of metal parts.
